Marketing mess to brand success : 30 challenges to transform your organization's brand (and your own)! - Miller, Scott Jeffrey (Tantor Media, Inc., 2021)
"Owning your mess and being vulnerable makes you an even stronger leader and Scott Miller shows you exactly how."--Dave Hollis, bestselling author of Get out of your own way. One man's mistake is another man's lesson. Don't let Scott Miller's success story fool you. He has made and learned from many mistakes in his career. Featuring thirty chapters with challenges like "A Name is Not a Lead" and "Hire People Smarter Than You," Marketing mess to brand success shares a career worth of horrifying mistakes, missteps, and lessons learned. Whether you're starting a new company, a brand manager figuring out the best brand strategy or brand positioning for a niche market, or trying to land your first job as a marketing manager or brand manager, this book is designed to prepare you for many of the inevitable challenges that you will encounter. Avoid marketing messes and square up to successes. A marketing crash course will not make you a marketing star. But having a better understanding of the role of marketing in business development and making sure you're focused and aligned with the right areas of an organization may. Each chapter features true stories and relevant questions that challenge you to become a better marketing manager